THE EFFORTS OF MAINTAINING TORAJAN LANGUAGE AS A MOTHER TONGUE OF TORAJAN PEOPLE FROM THE THREAT OF EXTINCTION: A PRELIMINARY STUDY - Patiung, Naomi; Sitoto, Simon (Linguistik, Terjemahan, Sastra (LINGTERSA), 2021)
This research aims to describe some efforts to maintain Toraja language as the mother language of Torajan people from the threat of extinction. This paper used a qualitative descriptive study. As it is conceptual writing of a preliminary study, this paper only presents some examples of the two varieties of Torajan language used in society. It proposes some suggested efforts on how to anticipate the extinction of the language concerned in the future. The results indicate some very important suggested efforts to maintain the two varieties (ordinary language and ritual language as used in both thanksgiving ceremony called Rambu Tuka' and death ceremony called Rambu Solo') of Torajan language that requires attention from different parties. As a part of Torajan culture, Torajan language in various uses contains values and norms as the local wisdom. Therefore, various parties should involve in its maintenance, such as governmental institutions, educational institutions, social institutions, and religious institutions in doing research, providing various written documentations, and socializing or disseminating them among the community in general and the schools at all levels in particular for continuous consumption.